Effects of pH and urea on the conformational properties of subtilisin DY. - Ricchelli, F (1982)
Subtilisin DY is very resistant to the denaturing action of urea: the conformational properties are not affected up to 4.5 M-urea, and even in the presence of 8 M-urea there is only a slow loss of ordered structure and caseinolytic activity. C.d. and fluorescence-emission studies also show that this proteinase is stable in the 5.5-10.0 pH range, whereas below pH 5.5 a sharp denaturation occurs that is complete at pH 4.5. Protein denaturation leads to a change of the emission quantum yield; in particular, in the native protein, indole fluorescence is quenched by some amino groups. Moreover, subtilisin DY possesses two classes of tyrosine residues: one class of exposed residues titrates normally, with pKapp. = 10.24, whereas one class of partially buried or hydrogen-bonded residues ionizes with pKapp. = 11.58. In general, such conformational properties resemble those of other subtilisins. However, some differences occur: e.g., subtilisin DY is less stable at acidic pH values and its tyrosine residues are more accessible to the solvent. Such differences are probably due to small variations of the three-dimensional structure; e.g., subtilisin DY has a slightly lower alpha-helix content.